PHARMA EXPORT: COMFORTS AND CONFRONTS IN INDIA - Alamelu R; Amudha R; CRESENTA SHAKILA MOTHA L; Nalini R (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The objective of this study is to know the comforts and confronts faced by pharma companies in India. It is of case study approach and presented the Indian pharma export advantages, the Government initiatives toward the export market, problems, the recent US trademark legislation issues, and the opportunities in a nutshell. The predicted growth of Indian pharmaceutical market size is US 100 billion by 2025, because of spending habit of the customer on health care and their awareness on health insurance. Indian companies have focused on export prospects in both formal and informal markets globally. This approach has made the pharma industry to achieve US 45 billion by 2020 and aimed to position as sixth largest market among the world. Keeping the high credibility of serving quality products in the complex market, India has gained a strong reputation among the global place. Keywords: Indian pharmaceutical, Pharma export, US trademark legislation, Indian pharma initiatives.